Association of Smoking and Opioid Consumption with Bladder Cancer Staging - Reza Dehghaniathar; Asaad Moradi; Amirhossein Dianati (پزشکی بالینی ابن سینا)
Background and Objective: Bladder cancer is the 10th most common cancer worldwide, affecting six million people annually. In recent studies, the relationship of this cancer with opioid consumption and smoking was demonstrated. The present study aimed to assess the frequency of smoking and opioid use in patients with bladder cancer and the relationship between these risk factors and bladder cancer staging. Materials and Methods: This multi-central cross-sectional study was performed on all bladder cancer patients who were referred to Firoozgar and Rasoul-e-Akram Hospitals (Tehran, Iran) from 2018 to 2022. The patient’s characteristics and habitual history, including smoking and opioid consumption, were analyzed. Opioid use and smoking correlation with cancer stage and the correlation between age and tumor stage were evaluated by Chi-square tests and point biserial correlation coefficient test, respectively. Results: A total of 499 patients were included. The mean age was 69.13 years. Regarding gender, 83.97% of patients were male. Moreover, 36.67% and 19.44% of subjects had a history of smoking and opioid consumption, respectively. In terms of stage, 19.04%, 27.45%, 25.85%, and 27.66% had been diagnosed with stages 1, 2, 3, and 4 bladder cancer. Smoking, as well as opioid use, had a significant relationship with the bladder cancer stage (P<0.001). Conclusion: Data from 499 patients were analyzed, and the results indicated no significant relationship between the gender of patients and the stage of bladder cancer. Furthermore, smoking and opioid consumption displayed a significant relationship with the stage of bladder cancer. In the current study, smoking and opioid consumption demonstrated a significant relationship with the stage of bladder cancer.